A commentary on Quintus of Smyrna Posthomerica V - James, Alan (Mnemosyne, Supplements, 2000)
The Posthomerica of Quintus of Smyrna is the only surviving Greek epic that gives a full narrative of the Trojan War between the Iliad and the Odyssey. Book V covers the contest between Ajax and Odysseus over the armour of Achilles, leading to Ajax' madness, suicide and funeral. The book gives balanced treatment to matters of text, language, literary qualities and sources. An introduction discusses the poem's main features. The commentary is punctuated by introductions to sections. There are indexes of subjects, ancient and mediaeval literature and Greek words. The work's major areas of interest are: influence of the Homeric epics, Quintus' use of later sources, the Trojan War in Greek and Latin literature, and Greek cultural history under the Roman Empire. This is the first full-length commentary on the book.